Scally: The Story of a Perfect Gentleman - Hay, Ian, 1876-1952 (Salt Lake City, UT : Project Gutenberg, 2009)
"Scally: The Story of a Perfect Gentleman" by Ian Hay is a humorous novel written in the early 20th century. The book chronicles the adventures of a family and their beloved dog, Scally, an amusingly inept but lovable creature. This light-hearted tale explores themes of companionship and the everyday trials and tribulations of pet ownership. The storyline primarily follows a couple, the husband and wife, as they navigate the challenges of finding and raising a dog, ultimately adopting a puppy they name Excalibur, affectionately called Scally. Through various comical episodes, Excalibur becomes an integral part of their life, often complicating matters for the family while providing them with joy. The narrative showcases Scally's antics, his interactions with the villagers, and the warmth his presence brings to the household. As the story unfolds, Scally proves to be not just a pet but a genuine part of the family's adventures and misadventures, illustrating the profound bond between humans and their canine companions. (This is an automatically generated summary.)
Release date is 2009-04-04
E-text prepared by Juliet Sutherland, Emmy, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Dogs -- Fiction